ANALISIS KINERJA KEUANGAN PADA PT BANK CENTRAL ASIA, TBK BERDASARKAN RASIO LIKUIDITAS, SOLVABILITAS, DAN PROFITABILITAS - Purwaningtyas, Titik; Widyaningrum, Puput Ria Edhi (JURNAL LENTERA AKUNTANSI, 2025)
The success of PT Bank Central Asia, Tbk in innovating products and services that meet the needs of customers, has made BCA receive attention from the public and investors. The success of a bank can also be seen from its financial statements which reflect the ability to generate profits, manage assets, pay liabilities and optimize capital. The purpose of this study was to determine the condition of the financial statements, determine the calculation of financial ratio analysis and interpretation of the results of ratio analysis at PT Bank Central Asia, Tbk. This research uses quantitative descriptive method using data obtained from literature and field studies. Based on the results of data analysis shows the financial condition of PT Bank Central Asia, Tbk in a healthy state when viewed from the liquidity ratio, solvency ratio, and profitability ratio. Which means PT Bank Central Asia must maintain and also improve its financial health by paying attention to the balance between assets, liabilities and equity to maximize net income from its income.